Unemployment, Growth and the Organisation of Work - Henri L.F. de Groot; Anton B.T.M. van Schaik (Tinbergen Institute, 2002)
We develop a two-sector endogenous growth model with a dual labour market resulting from the presence of an effort extraction function in one sector. Effort of workers can be influenced by pay and monitoring. This results in an endogenous non-competitive wage differential between sectors and a monitoring intensity that is a source of fixed costs for the firm. Growth is driven by investments in R&D performed in the high-wage sector. Unemployment is determined by the costs and benefits of waiting for a high-paid job. The wage structure, growth, and unemployment are shown to depend on the way effort is extracted.
Keywords: E24; J21; J53; O41; 330; endogenous growth; unemployment; effort extraction; dual labour market; Arbeitsmarktsegmentation; Arbeitslosigkeit; Arbeitsorganisation; Neue Wachstumstheorie; Theorie